2021
DOI: 10.1109/emr.2021.3108889
|View full text |Cite
|
Sign up to set email alerts
|

The Continuity of Learning

Abstract: ASan educator and researcher my ultimate goal is to impart knowledge and encourage learning. We are also well aware that learning does not end at the classroom door.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Triangulation showed that the most analysed technologies in the literature were IoT (Rajput & Singh, 2020), BDA (Xiang & Xu, 2019), blockchain (Choi et al, 2020), AM (Colorado et al, 2020) and AI (Wilts et al, 2021). The least cited were quantum computing (Sarkis, 2021), drones (Mahroof et al, 2021), AV (Prideaux & Yin, 2019), AR (Kerin & Pham, 2020) and advanced robotics (Tozanlı et al, 2020). The intermediaries with a respective frequency of 9 and 8 were cloud computing and smart manufacturing.…”
Section: Fd Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Triangulation showed that the most analysed technologies in the literature were IoT (Rajput & Singh, 2020), BDA (Xiang & Xu, 2019), blockchain (Choi et al, 2020), AM (Colorado et al, 2020) and AI (Wilts et al, 2021). The least cited were quantum computing (Sarkis, 2021), drones (Mahroof et al, 2021), AV (Prideaux & Yin, 2019), AR (Kerin & Pham, 2020) and advanced robotics (Tozanlı et al, 2020). The intermediaries with a respective frequency of 9 and 8 were cloud computing and smart manufacturing.…”
Section: Fd Resultsmentioning
confidence: 99%
“…Some of the technologies are at more advanced stages of maturity (e.g. cloud computing, BDA and IoT) in research and industry applications, while others such as quantum computing (Sarkis, 2021) are still in the early stages of development. Remarkably, although blockchain applications are only starting to be implemented in industry (Kouhizadeh et al, 2020), blockchain itself has already attracted considerable academic attention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations